Professional Training of Teachers and the Problems of Their Self-Awareness - Galiakberova, Alfinur A.; Khakimova, Nailya Gazizovna; Khusnutdinova, Rezida Rustamovna; Gao, Dapeng (Journal of History Culture and Art Research, 2020)
This article considers the problem of future teachers’ professional self-awareness enhancement in preparing for effective professional activity. The current knowledge paradigm in professional pedagogical education does not ensure the progress of future teachers’ professionally important qualities, such as professional self-awareness, a set of future teachers’ knowledge of their inner world, abilities, and self-evaluation. The review of some special issues reveals a decreasing motivation, partial loss of valuable attitude to teaching career of pedagogical students possessing theoretical knowledge, practical skills acquired in the course of high school special training. Nowadays there are constantly conducted studies of students ’personal characteristics and their ideas about themselves. However, experiments on the dynamics of future teachers' ideas about themselves as future professionals are not carrying out. This paper highlights substantiation of the relevance and importance of this problem in terms of professional self-determination and future teachers’ personality formation. It discovers approaches to professional self-awareness of modern future teachers’ enhancement. Modeling of a common pedagogical system with interrelated structural components and stages united by students’ professional self-awareness progress strategy presents a specially organized resource to solve this problem. Compliance with the developed complex of organizational and pedagogical conditions ensures progress in professional self-awareness of future teachers in the light of the selected criteria and indicators of this complex personal structure formation.